Aesthetics Today : Contemporary Approaches to the Aesthetics of Nature and of Arts. Proceedings of the 39th International Wittgenstein Symposium in Kirchberg - Majetschak, Stefan; Weiberg, Anja (Publications of the Austrian Ludwig Wittgenstein Society - New Series ;, 2017)
Aesthetics is no longer merely the philosophy of perception and the arts. Nelson Goodman, Arthur Danto and others have contributed to develop aesthetics from a field at the margins of philosophy to one permeating substantial areas of theoretical and practical philosophy. New approaches like environmental and ecological aesthetics widened the understanding of the aesthetics of nature. The contributions in this volume address the most important issues in contemporary aesthetics, many of them from a Wittgensteinian perspective. The 39th International Ludwig Wittgenstein Symposium, organized by the Austrian Ludwig Wittgenstein Society, was held at Kirchberg am Wechsel, Lower Austria, from August 7th to 13th 2016 and aimed at taking an inventory of important tendencies and positions in contemporary aesthetics. The volume includes a selection of the invited papers.